Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1980
DOI: 10.4039/ent112219-2
|View full text |Cite
|
Sign up to set email alerts
|

A NOTE ON PELECINUS POLYTURATOR (HYMENOPTERA: PELECINIDAE), A PARASITE OF PHYLLOPHAGA ANXIA (COLEOPTERA: SCARABAEIDAE)

Abstract: The common June beetle, Phyllophaga anxia (LeConte), is an indigenous pest of agricultural crops in North America (Hammond 1948; Ritcher 1949). A bionomic study and survey for natural enemies of P. anxia was conducted in southern Quebec from 1975 to 1977. Pasture soils were searched for immature stages of P. anxia, and any natural enemies found in situ were collected. A prepupa and pupae of Pelecinus polyturator (Drury) were found in the pasture on several occasions. Previously, P. polyturator had been reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Pelecinus was ® rst reported to have been reared from larvae of L achnosterna Hope (= Phyllophaga Harris, Coleoptera: Scarabaeidae, Melolonthinae) by Forbes ( 1894). Since then, Hudson ( 1920) , Petch and Hammond ( 1926 ), Fattig ( 1944), Hammond ( 1944) and Lim et al ( 1980 ) have reared the species in the northern part of its range from larvae of Phyllophaga. Lim able to specify the host species as Phyllophaga anxia ( LeConte).…”
Section: Biologymentioning
confidence: 98%
“…Pelecinus was ® rst reported to have been reared from larvae of L achnosterna Hope (= Phyllophaga Harris, Coleoptera: Scarabaeidae, Melolonthinae) by Forbes ( 1894). Since then, Hudson ( 1920) , Petch and Hammond ( 1926 ), Fattig ( 1944), Hammond ( 1944) and Lim et al ( 1980 ) have reared the species in the northern part of its range from larvae of Phyllophaga. Lim able to specify the host species as Phyllophaga anxia ( LeConte).…”
Section: Biologymentioning
confidence: 98%
“…No adult wasp emerged from collected grubs. The wasp has been reported as an endoparasite of grubs of Phyllophaga spp., including P. anxia (FORBES 1894;DAVIS 1919;PETCH andHAMMOND 1925, 1926;BRUES 1928;HAMMOND 1944;LIM et al 1980). Quantitative data unfortunately are few and it is difficult to assess the impact of pelecinids on white grub populations.…”
Section: Insect Parasites and Predators Of Phyllophaga Anxia In Quebecmentioning
confidence: 99%
“…As far as the habit of these animals is concerned, they are koinobiont endoparasites. They are usually found parasitizing beetle larvae of the Phyllophaga Harris, 1827 genus (Scarabaeidae), using their huge and flexible specialized metasoma to penetrate the soil and encounter the larvae (Lim & Stewart 1980;Mason 1984). More details of this host-seeking behavior were obtained by Bennett (2003), who demonstrated that females can reach larvae that are around 5 cm below the soil surface, inserting the entire metasoma into the soil and even a portion of the mesosoma.…”
mentioning
confidence: 99%